2007
DOI: 10.1158/1078-0432.ccr-06-3072
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Tumor Growth and Angiogenesis in Ovarian Carcinoma by Targeting the Nuclear Factor-κB Pathway

Abstract: Purpose: Curcumin, a component of turmeric, has been shown to suppress inflammation and angiogenesis largely by inhibiting the transcription factor nuclear factor-nB (NF-nB). This study evaluates the effects of curcumin on ovarian cancer growth using an orthotopic murine model of ovarian cancer. Experimental Design: In vitro and in vivo experiments of curcumin with and without docetaxel were done using human ovarian cancer cell lines SKOV3ip1, HeyA8, and HeyA8-MDR in athymic mice. NF-nB modulation was ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
269
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(285 citation statements)
references
References 40 publications
(30 reference statements)
7
269
0
5
Order By: Relevance
“…We have found that (a) the combination of curcumin and gemcitabine inhibits pancreatic cancer growth in nude mice by inhibiting NF-kB regulated gene expression, cell proliferation, and angiogenesis [144]; (b) the combination of curcumin and docetaxel is effective against human ovarian cancer in nude mice [142]; (c) curcumin can suppress the growth of human glioblastoma in rodents [77]; and (d) curcumin sensitizes colon cancers in nude mice to oxaliplatin [137]. In addition, other recent studies have shown that curcumin sensitizes prostate cancers to chemotherapeutics and radiation by downregulating expression of the MDM2 oncogene [82].…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…We have found that (a) the combination of curcumin and gemcitabine inhibits pancreatic cancer growth in nude mice by inhibiting NF-kB regulated gene expression, cell proliferation, and angiogenesis [144]; (b) the combination of curcumin and docetaxel is effective against human ovarian cancer in nude mice [142]; (c) curcumin can suppress the growth of human glioblastoma in rodents [77]; and (d) curcumin sensitizes colon cancers in nude mice to oxaliplatin [137]. In addition, other recent studies have shown that curcumin sensitizes prostate cancers to chemotherapeutics and radiation by downregulating expression of the MDM2 oncogene [82].…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…Several studies, also, report that it is an agent possessing a wide variety of biological and pharmacological activities, including anti-proliferation (Choi et al, 2006), antiapoptosis (Aggarwal et al, 2008), anti-angiogenesis (Lin et al, 2007) and inhibition of cell invasion and metastasis (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Parthenolide is a plantderived sesquiterpene lactone whereas curcumin is a derivative of the spice turmeric (Curcuma longa). Both of them are widely used to inhibit the DNA binding of NF-kB proteins as well as the IkB kinase in cellular or animal tumor models (Oka et al, 2007;Kishida et al, 2007;Lin et al, 2007;Marin et al, 2007). First of all, we demonstrated that inhibition of the NF-kB pathway resulted in the normalization of the transcriptional activity of the cyclin D1 gene promoter in the low-menin expressing AS303 cells.…”
Section: Discussionmentioning
confidence: 99%